AL FALAH CONCEPT SUPPORT BUSINESSMAN MUSLIM WHICH SUCCESS - Z. Hrp, Ade Khadijatul; MM, Rahmat (Proceeding International Seminar of Islamic Studies, 2023)
The study of Islamic entrepreneurship and its relationship with success has not been widely developed by Islamic scholars. In the Review and Research Agenda, a collection of impact studies, most of the research showing religiosity and spirituality on entrepreneurship was developed by non-Muslim scholars. So there is a clear gap in this field. The purpose of this article is to explain the entrepreneurial concept of Al Falah among Muslim entrepreneurs . This research is required in the form of a literature survey where researchers use secondary sources such as articles, papers, and scientific discourse to explain the supporting concepts of successful Muslim entrepreneurs. From the results of a literature survey, researchers basically found that: Muslim entrepreneurs who are successful in terms of Muslim muamalah, not only have good personalities in entrepreneurial activities, but at the same time follow religious instructions. In an Islamic perspective, the balance of entrepreneurs achieving worldly success while fulfilling religious and sharia requirements is known as 'Al Falah' entrepreneurs. In other words, the concept of al-falah is an extraordinary achievement that covers all aspects of human life such as having spiritual, material, and moral qualities to succeed in this life and the next.